Modulation of non-bilayer lipid phases and the structure and functions of thylakoid membranes: effects on the water-soluble enzyme violaxanthin de-epoxidase - Dlouhý, Ondřej; Kurasová, Irena; Karlický, Václav; Javornik, Uroš; Šket, Primož; Petrova, Nia Z; Krumova, Sashka B; Plavec, Janez; Ughy, Bettina; Špunda, Vladimír; Garab, Győző (Scientific reports, 2020)
The role of non-bilayer lipids and non-lamellar lipid phases in biological membranes is an enigmatic problem of membrane biology. Non-bilayer lipids are present in large amounts in all membranes; in energy-converting membranes they constitute about half of their total lipid content-yet their functional state is a bilayer. In vitro experiments revealed that the functioning of the water-soluble violaxanthin de-epoxidase (VDE) enzyme of plant thylakoids requires the presence of a non-bilayer lipid phase. 31P-NMR spectroscopy has provided evidence on lipid polymorphism in functional thylakoid membranes. Here we reveal reversible pH- and temperature-dependent changes of the lipid-phase behaviour, particularly the flexibility of isotropic non-lamellar phases, of isolated spinach thylakoids. These reorganizations are accompanied by changes in the permeability and thermodynamic parameters of the membranes and appear to control the activity of VDE and the photoprotective mechanism of non-photochemical quenching of chlorophyll-a fluorescence. The data demonstrate, for the first time in native membranes, the modulation of the activity of a water-soluble enzyme by a non-bilayer lipid phase.
Keywords: teplota; epoxidové sloučeniny; Calorimetry, Differential Scanning; oxidoreduktasy; tylakoidy; Water; voda; xanthofyly; Magnetic Resonance Spectroscopy; světlo; Lipids; koncentrace vodíkových iontů; Solubility; Xanthophylls; lipidové dvojvrstvy; Epoxy Compounds; Lipid Bilayers; magnetická rezonanční spektroskopie; Light; Kinetics; kinetika; diferenciální skenovací kalorimetrie; Thylakoids; Spinacia oleracea; Oxidoreductases; rozpustnost; Hydrogen-Ion Concentration; Temperature; lipidy